Le impronte del paesaggio sonoro: un’opportunità per la didattica della storia e della geografia - Rocca, Lorena (Ri-Vista. Research for landscape architecture, 2015)
The essay aims to the outline the first thoughts flourished within an interdisciplinary research group of musicologists, musicians, historians and education experts, who are inquiring in both theoretical and practical ways to approach resonant landscapes: «The ear has to be sensitive to the marvellous world of sounds surrounding us» has been the first challenge faced by the group, starting from the first definition of “resonant landscape” by R.M. Schäfer (1977). Every landscape has its peculiar and unique sounds. They are determined by the perceptive ways, used by the individuals and the groups of people, as “resonant imprinting” able to connote a type of culture, able to contribute, together with other human expressions, to create the local identity. giving voice to these perceptions means to trigger paths of reflection and of listening education allowing to amplify a sensory channel that tends to be more and more neglected by the western culture.